2009
DOI: 10.1007/s11307-009-0199-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Airway Distribution of Transnasal Solutions in Mice by PET/CT Imaging

Abstract: Purpose: Transnasal administration is one of the most common routes for allergen challenge in mouse models of airway diseases. Although this technique is widely used, neither the amount of allergen that reaches the lung nor its airway distribution has been well established. We used positron emission tomography (PET) and computed tomography (CT) to examine the anatomical distribution of a solution containing a tracer immediately after transnasal delivery and to determine the possible influence of age and admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Although the anatomy below the upper trachea could not be imaged in this nasal airway study it is likely that fluid reached further into the lung airways, a finding consistent with a recent low-resolution radiotracer study. 7 The results also supports our finding that long term gene expression was produced in the lung by a lentiviral vector containing the luciferase transgene that was delivered to the nose and was designed specifically to produce nasal airway gene transfer. 22 It follows that smaller gene vector doses might be able to produce the same levels of gene expression in the anterior nasal airways.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the anatomy below the upper trachea could not be imaged in this nasal airway study it is likely that fluid reached further into the lung airways, a finding consistent with a recent low-resolution radiotracer study. 7 The results also supports our finding that long term gene expression was produced in the lung by a lentiviral vector containing the luciferase transgene that was delivered to the nose and was designed specifically to produce nasal airway gene transfer. 22 It follows that smaller gene vector doses might be able to produce the same levels of gene expression in the anterior nasal airways.…”
Section: Discussionsupporting
confidence: 84%
“…Small-animal CT, and to a lesser extent MRI, which provide 3-dimensional (3D) information via tomographic approaches, could be used to examine murine airways but the time to acquire 3D data sets prohibits tracking of high speed dynamic events such as fluid dosing at high spatial resolutions. Although PET-CT has been used to show the final location of trans-nasally delivered solutions 7 , the acquisition speed and spatial resolution of PET is very low, the dynamics of the fluid delivery cannot be imaged, the air containing spaces are poorly defined by CT and the spatial resolution is insufficient. None of these methods can visualize fluid movement in mouse airways at high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, intranasal delivery of compounds into mice results in a low efficiency, highly variable delivery of reagents into the target organ of the lung. Intranasal delivery of Positron Emission Tomography (PET) imaging reagents to the murine lung yielded a 40% delivery efficiency 11 , whereas we have demonstrated that IMIT offers an excellent alternative to other lung delivery approaches with its >98% delivery efficacy and multilobar distribution. This improvement in targeted delivery to the lung has the potential to increase the reproducibility of therapeutic delivery for treatment of pulmonary disease.…”
Section: Discussionmentioning
confidence: 95%
“…Groups of mice were immunized by intraperitoneal injections of 5-μg Dermatophagoydes pteronyssinus (HDM, Alk-Abelló, Spain) complexed with 2-mg aluminum potassium sulphate (Alum, Sigma Chemical Co., St Louis, Mo) on days 0 (D0) and 4 (D4). On D14 and D15, mice were challenged with 5-μg HDM delivered intranasally [ 21 ] after slight anesthesia. Additional experiments were performed with chicken egg albumin (OVA, Sigma) plus Alum as described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%